Faktor-Faktor yang Mempengaruhi Adopsi QRIS pada Generasi Milenial: Aplikasi Technology Acceptance Model (TAM) - Muhammad Zaky Irham; Muhammad Fikri Tanjung (Jurnal Sistem Informasi Komputer ( SIKOM ), 2026)
This study aimed to analyze the determinant factors influencing the accelerated adoption of the Quick Response Code Indonesian Standard (QRIS) among the Millennial Generation in Indonesia. The research employed the Technology Acceptance Model (TAM) as the main theoretical framework to explain user acceptance behavior toward digital payment systems. The population of this study consisted of millennials who actively use QRIS services across various regions in Indonesia. A non-probability sampling method with a purposive sampling technique was applied, using the criterion that respondents must have used QRIS at least once. Primary data were collected through online questionnaires distributed to 48 respondents.The demographic results showed that most respondents were female (67%) and predominantly within the productive age range of 21–25 years (38%). Data analysis was conducted in two stages, namely descriptive analysis and inferential analysis using Partial Least Squares–Structural Equation Modeling (PLS-SEM), which is considered appropriate for exploratory research with a relatively small sample size. Descriptive findings indicated that respondents exhibited positive perceptions of all TAM variables, with mean values ranging from 3.7 to 4.2 on a five-point Likert scale. Furthermore, the outer model evaluation confirmed that all constructs. Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Behavioral Intention to Use, and Actual Use met the criteria for convergent validity and reliability. Overall, the results demonstrate that the TAM model is valid and reliable in predicting QRIS adoption behavior, highlighting that perceived benefits and ease of use play a crucial role in shaping millennials’ intention and actual usage of QRIS.